Antibacterial, Antifungal and Anticancer Activity of Five Strains of Soil Microorganisms Isolated From Tangkuban Perahu Mountain by Fermentation - Desak Gede Sri Andayani; Ukan Sukandar; Elin Y. Sukandar; I. Ketut Adnyana (Bogor Agricultural University, Indonesia, 2015)
Microorganisms were isolated from soil taken from Tangkuban Perahu mountain. Five strains were investigated in this study, designated TP1, TP2, TP3, TP4, and TP5, respectively. Morphological, biochemical and molecular identifications were conducted for all five strains. These isolates were shown to be closely related to Nocardia sp. YIM 65630 (90%), Streptomyces galbus (99%), Aspergillus unguis (86%), Paecilomyces marquandii (100%) and Nocardia niigatensis (95%), respectively. Production of antibacterial, antifungal and anticancer metabolites was done by fermentation. Screening for bioactivity of five isolates was done by testing the fermentation broth against resistant and pathogenic bacteria, fungi and T47D breast cancer cell line. TP2 strain showed the best bioactivity; the metabolite was purified by extraction with ethyl acetate. Antibacterial, antifungal and anticancer activities from the ethyl acetate extract of TP2 strain were tested by agar diffusion, microdilution and MTT. The extract was shown to be active against methicillin resistant Staphylococcus, methicillin sensitive Staphylococcus aureus, methicillin resistant coagulase negative Staphylococcus, vancomycin resistant Enterococcus, Escherichia coli, Microsforum gypseum with the minimum inhibitory concentration (μg/mL) and diameter of inhibition (mm): 150, 35; 150, 30; 300, 35; 300, 35; 300, 29; 4.7, 36, respectively. The IC50 value of the T47D cell line was 457 μg/mL.